Evaluation of Cassava Leaf Paste on Egg Performance and Egg Quality of Quail Egg Laying Period - La Jumadin; Aryani Sismin Satyaningtijas; Hera Maheshwari; Niken Ulupi; Dwi Nurhidayah Zubaidah; Maryce Agusthinus Walukou; Lili Darlian; Damhuri; Koekoeh Santoso (IPB University, 2024)
Quail has a high egg production. On the other hand, quail has a weakness, which is prone to stress. This stress is caused by erratic weather conditions. This study examines and evaluates the role and function of cassava leaf paste on aspects of egg performance and egg quality of quail eggs in the laying period that are reared under natural conditions or normal conditions in tropical areas, such as in Indonesia. Observation of egg performance was detected by calculating egg length, egg width, and egg shape index. Observation of egg quality aspects was detected by calculating the quality of the shell, egg white, and egg yolk. The results showed that the shape index of quail eggs at various levels of cassava leaf paste administration showed results that were not significantly different. The egg shape index obtained at P2 and P3 tends to be more oval/semi-tapered, while at P0 and P1 it tends to be round. The value of the eggshell weight, egg white weight, and egg yolk weight that received cassava leaf paste were higher than the control treatment. The high eggshell weight, egg white weight, and egg yolk weight were suspected to be differences in nutritional content, mineral elements, and flavonoids between treatments. Giving cassava leaf paste can increase the index of egg shape in the quail laying period. The application of cassava leaf paste can also increase the weight of the shell, the weight of the egg white, and the weight of the yolk in the egg-laying period of quail.